ENHANCING SUSTAINABLE DEVELOPMENT AT LOCAL LEVEL: A STUDY OF UNESCO’S INITIATIVE THROUGH CREATIVE CITIES NETWORK - Luerdi Luerdi (Sultan Syarif Kasim State Islamic University, Riau, 2023)
Sustainable development is a global shared agenda that has been discussed by global communities. Such agenda has, too, been a strong commitment among cities thanks to the role of international organizations like UNESCO with its initiative called the UNESCO Creative Cities Network (UCCN). Through the Network, UNESCO has contributed to enhancing sustainable development at the local level in terms of the development of creative and cultural industries. This study aims to describe such a role with a few specific objectives; to shed light on what norm the organization has embraced, how it has influenced membership of cities and maintained their commitment, and how it has promoted intercity cooperation. This research applied the qualitative method and the constructivist approach as well as the concept of norm entrepreneurship. The findings demonstrate that UNESCO plays its role as a norm entrepreneur in which sustainable development has been a global norm constructing its shared identity and conviction. Performing as a norm entrepreneur, UNESCO acts upon the role of agenda-setting and norm advocacy to introduce the idea of the UCCN and convince cities of the importance of sustainable urban development through creative assets. While socialization and the Network’s membership application process contribute to diffusing the norm to the cities, reporting and monitoring are projected to be mechanisms to maintain the membership commitment. Finally, gathering events within the UCCN platform offers the opportunity to cooperate and strengthen ties between member cities as a further way to institutionalize the norm. This paper offers a perspective that international organizations with significant normative power and policy innovation turn them into important actors in global politics of sustainable development.